2018
DOI: 10.1103/physrevb.98.165423
|View full text |Cite
|
Sign up to set email alerts
|

Gap formation in helical edge states with magnetic impurities

Abstract: Helical edge states appear at the surface of two dimensional topological insulators and are characterized by spin up traveling in one direction and the spin down traveling in the opposite direction. Such states are protected by time reversal symmetry and no backscattering due to scalar impurities can occur. However, magnetic impurities break time reversal symmetry and lead to backscattering. Often their presence is unintentional, but in some cases they are introduced into the sample to open up gaps in the spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…One way to examine the topological stability is to probe the energy spectrum of topological insulators in the presence of randomly distributed ionized and magnetized impurities. The conducting surface states of these materials are robust against the effect of non-magnetic disorder, while the Dirac surface state spectrum can be gapped by magnetic impurities or other perturbations breaking timereversal symmetry [16][17][18][19][20][21][22][23]. Nevertheless, a well-defined band-gap is not always formed by magnetic impurities, as observed in some experiments [24][25][26].…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…One way to examine the topological stability is to probe the energy spectrum of topological insulators in the presence of randomly distributed ionized and magnetized impurities. The conducting surface states of these materials are robust against the effect of non-magnetic disorder, while the Dirac surface state spectrum can be gapped by magnetic impurities or other perturbations breaking timereversal symmetry [16][17][18][19][20][21][22][23]. Nevertheless, a well-defined band-gap is not always formed by magnetic impurities, as observed in some experiments [24][25][26].…”
Section: Introductionmentioning
confidence: 92%
“…The difference between t-matrix approximation and self-consistent t-matrix approximation is that the former uses the unperturbed Green's function, while in the latter the impurity averaged Green's function is used in the t-matrix expansion. In the self-consistent t-matrix approximation, the t-matrix expansion is given by [20,39,40]…”
Section: Model and Formalismmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, it was shown that the presence of magnetic impurities at the surface of TIs may lead to the in-plane magnetoresistance which is a mixture of the anisotropic and spin magnetoresistance, as well as to planar Hall effect 29 . Moreover, random magnetic impurities may lead to opening an energy gap for the edge states [30][31][32] , and also may improve quality of the quantum anomalous Hall effect in magnetic TIs 33 . Recently the electron states at the surface of a TI attached to a ferromagnet, described by the XY model, have also been considered, and it was shown that the classical magnetic fluctuations in the ferromagnet could be mapped onto the problem of Dirac fermions in the random magnetic field 34 .…”
mentioning
confidence: 99%